PENGARUH PENERAPAN METODE PEMBELAJARAN CROSSWORD PUZZLE BERBASIS APLIKASI PUZZLE MAKER TERHADAP HASIL BELAJAR GEOGRAFI SISWA KELAS XI IIS DI SMA PEMBANGUNAN LABORATORIUM UNP - Putri, Novita Sari; Novio, Rery (JURNAL BUANA, 2023)
This study aims to determine the effect of applying the crossword puzzle learning method based on the puzzle maker application on geography learning outcomes at the UNP Development Laboratory High School. This type of research is quantitative, using the true experimental design method. The research subjects were class XI IIS 1 as the experimental class and class XI IIS 3 as the control class. For the sampling technique using purposive sampling with a total sample of 60 people. The data in this research is in the form of student achievement tests in class XI IIS. With data collection techniques in the form of interviews, using learning outcomes tests namely pretest and posttest as well as documentation. Whereas for data processing using individual completeness, normality test, homogeneity test, and T test to determine the hypothesis. The results showed that the Crossword Puzzle method based on the Puzzle Maker application applied in the experimental class could significantly influence student learning outcomes in the subject of natural resource management in Indonesia. This can be seen from the average results of student learning outcomes taught using the Crossword Puzzle method based on the Puzzle Maker application, before applying the Crossword Puzzle method based on the Puzzle Maker application in the experimental class, the average result was 50.1. However, after applying the Crossword Puzzle method based on the Puzzle Maker application in the experimental class, the average value was 82.6. While the results of data analysis using the T test obtained a tcount of 4.565 > ttable of 2.048, so it can be concluded that the Crossword Puzzle method based on the Puzzle Maker application has an effect on learning outcomes. Keywords : Crossword Puzzle, Learning Outcomes, Puzzle Maker.